Tinjauan Hukum Mengenai Penetapan Pengadilan Negeri Yang Mengabulkan Izin Perkawinan Pasangan Beda Agama Dihubungkan Dengan Peraturan Perundang-Undangan Terkait - Rizky Prameswari; Djanuardi Djanuardi; Betty Rubiati (Hakim, 2023)
The right to marry and to find a family through legal marriage is the right of every citizen guaranteed in the Indonesian state constitution. In Indonesia's positive law, a valid marriage is a marriage that takes place based on the laws of each religion and belief. Indonesia is a plural country consisting of various tribes, races, and religions. As a result of this pluralism, interfaith marriages occur like it can see in the Court Decree No. 512/Pdt.P/2002/PN.Jkt.Tim and Court Decree No. 71/Pdt.P/2017/PN.Bla. Interfaith marriages are unwanted marriages in Islam, Christianity, and Catholicism. Likewise, the Law on Marriage does not regulate interfaith marriages. However, since the promulgation of the Law on Population Administration, it has provided an opportunity for interfaith marriages to occur through a Court Decree. The purpose of this research is to find out the validity of interfaith marriage and the validity of court decree about approval interfaith marriage associated with related laws and regulations. This research was conducted using a normative juridical approach based on applicable legal concepts and theories. Then, the data analysis method used is qualitative juridical. Based on the results of the study, the validity of interfaith marriages, when linked to the Law on Marriage, is invalid. However, the registration of marriages through a court order is a method that is recognized by law as an introduction so that interfaith marriages whose registration is rejected can be registered so as to obtain legal certainty for interfaith couples.